A Study of Consumer Behavior and Expectations on Information Reception on Facebook - Hoaihongthong, Suwannee; Panjanghan, Piyathida (Journal of Information and Learning [JIL], 2025)
This study aims to analyze consumer behavior and expectations towards news reception on Facebook, focusing on information-seeking behavior, media exposure, and the acceptance of technology influencing consumers’ news consumption behavior on Facebook. An online questionnaire was used to survey 400 Facebook users. The results were as follows. 1) Regarding information-seeking behavior, most users spent 1-5 hours per day consuming news on Facebook, with news pages being the primary channel for following news. The reliability of the sources was a key factor influencing news sharing, video reports and social news were the most popular. 2) Regarding media exposure, websites were another important channel for users to follow news. Attractive headlines were the main factor drawing users to the news, and pages of the users’ interests were followed for updates. Most users checked Facebook for news before bedtime and felt that Facebook provided easy access to news. 3) Concerning technology acceptance, users rated Facebook at the high level for its convenience in accessing news, its role in news exposure, and their intention to continue using it. However, the understanding of functions on Facebook, confidence in data security, adaptability to technological updates, and overall satisfaction with using Facebook for news updates were rated at the moderate level. These findings can be utilized to develop communication strategies on Facebook that align with consumer behavior and to enhance confidence in personal data security on the platform.